2006
DOI: 10.1007/s10701-006-9058-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Empty Spacetime a Physical Thing?

Abstract: This article deals with empty spacetime and the question of its physical reality. By "empty spacetime" we mean a collection of bare spacetime points, the remains of ridding spacetime of all matter and fields. We ask whether these geometric objects-themselves intrinsic to the concept of field-might be observable through some physical test. By taking quantum-mechanical notions into account, we challenge the negative conclusion drawn from the diffeomorphism invariance postulate of general relativity, and we propo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Already L. Janossy had shown that if an ether exists, it is undetectable and, therefore, relativistic, which can also be said of the Planck scale [59,60]. In other words, for the purposes of mathematical construction, the basic ontological elusibility is not important, as we have already seen in the case of 't Hooft and other highly speculative approaches of contemporary physics, where sometimes even the boundaries between geometry and physics fade [61]. In particular, the ultimate Newtonian objects, i.e., a mix of positive and negative masses, each one allocated in a Planck cell, was in its initial form the kind of naive hypotheses in contrast with particle physics, despite attempts to show at least the theoretical plausibility of H. Bondi and later by B. Bonnor [62,63].…”
Section: Winterberg's Planck Plasma: An Exactly Non-relativistic Theorymentioning
confidence: 99%
“…Already L. Janossy had shown that if an ether exists, it is undetectable and, therefore, relativistic, which can also be said of the Planck scale [59,60]. In other words, for the purposes of mathematical construction, the basic ontological elusibility is not important, as we have already seen in the case of 't Hooft and other highly speculative approaches of contemporary physics, where sometimes even the boundaries between geometry and physics fade [61]. In particular, the ultimate Newtonian objects, i.e., a mix of positive and negative masses, each one allocated in a Planck cell, was in its initial form the kind of naive hypotheses in contrast with particle physics, despite attempts to show at least the theoretical plausibility of H. Bondi and later by B. Bonnor [62,63].…”
Section: Winterberg's Planck Plasma: An Exactly Non-relativistic Theorymentioning
confidence: 99%
“…Because spacetime is identified with the manifold, metrical field and metrical relations are extrinsic to it. The manifold functions as a substratum -or geometrical ether (Meschini andLehto 2006, 1206) -which supports physical fields including the metrical, with the provision that the metrical field is a different sort of field from other physical fields. This leads MS to a clear-cut separation of spacetime (as an ethereal container) and physical fields (as its fillers).…”
Section: Manifold Substantivalismsmentioning
confidence: 99%
“…The function of spacetime points is a physical task of localizing fields. Points are intrinsic to the very concept of the physical field (Meschini andLehto 2006, 1206). But how are the points individuated?…”
Section: Manifold Substantivalismsmentioning
confidence: 99%
“…Purpose of this paper is to show that there are regularities which result in a Euclidean-like space. The multiple space combined with the regularities offers a pregeometry of space, see for example reference [6] for this concept. To be a discrete alternative to continuous space, more results are required from wellchosen regularities or deviations of the space structure.…”
Section: Introductionmentioning
confidence: 99%